Refining method of ferrosilicon alloy
By using the combination of molten iron bottom blowing method and refining slag in the ferrosilicon alloy refining process, combined with the regulation of air and oxygen flow, the problem of controlling aluminum and calcium content in ferrosilicon alloys is solved, and efficient refining of low-calcium and ultra-low aluminum-ferrosilicon alloys is achieved, and the quality and output of the product are improved.
Patent Information
- Application Number
- CN202411890606.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to effectively control the content of aluminum and calcium in ferrosilicon alloys, especially when using ordinary raw materials to produce ultra-low aluminum-ferrosilicon alloys, resulting in difficult removal of impurities, long refining time, serious losses in the adhesive packet, and low product output and pass rate.
The iron-water-covered bottom blowing method is used to add refined slag to the mixed raw materials during the iron discharge process for refining. By adjusting the air and oxygen flow in the mixed blowing gas, the amount of refining slag and the time of blowing are controlled to achieve the refining of low-calcium and ultra-low aluminum-ferrosilicon alloys.
Effectively remove aluminum and calcium impurities in ferrosilicon alloys, improve the product pass rate and output, reduce the loss of sticky packets, and ensure that the calcium content is within the optimal value range, and the aluminum removal rate reaches more than 95%.
Smart Images

Figure CN119710143A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ferrosilicon alloy refining, and in particular relates to a ferrosilicon alloy refining method. Background Art
[0002] Ferrosilicon alloy is an alloy material smelted in an electric furnace using silica, carbon and iron products as raw materials. It can be used as a deoxidizer and alloying agent to improve the performance of steel. Ferrosilicon alloy is a deoxidizer in the steelmaking industry. Excessive aluminum content can cause quality problems and production safety hazards in steel. During the deoxidation and alloying process of ferrosilicon alloy, the presence of aluminum will form high-melting-point oxides that adhere to the inner wall of the nozzle to form nodules and block the nozzle, seriously affecting the casting process and the quality of steel. Therefore, the aluminum content in ferrosilicon alloy must be strictly controlled, especially when producing special steel grades, the requirements for aluminum are more stringent, and the aluminum content needs to be controlled below 0.1%.
[0003] Usually, the aluminum content entering the furnace is reduced by raw material control, but the requirement of aluminum content below 0.1% cannot be achieved by raw material control alone, and further dealumination must be combined with off-furnace refining. Off-furnace refining includes chlorination refining and oxidation refining. Chlorination refining has been basically discontinued due to its great harm to the environment and human body. At present, off-furnace refining is mainly based on oxidation refining. Oxidation refining is to use an oxidant to oxidize and volatilize the impurities in ferrosilicon alloys. The oxidant used can be a gas such as oxygen or a solid such as SiO2, CaO and Fe2O3.
[0004] Chinese invention patent application CN112375874A discloses a refining slag composition for off-furnace refining of ferrosilicon with an aluminum content of less than 0.1%. The raw materials are high-purity silica, petroleum coke and silicon steel sheets. The refining slag composition is used for dealumination. The composition is calculated by weight. The first refining slag is composed of 65 parts of quartz sand, 21 parts of lime, and 14 parts of fluorite. The addition amount is 10% of the total mass of the raw materials for ferrosilicon alloy smelting, and the overall refining time is 20 minutes. The second refining slag is composed of 70 parts of quartz sand, 28 parts of lime, and 25 parts of fluorite. The addition amount is 8% of the total mass of the raw materials for ferrosilicon alloy smelting, and the overall refining time is 25 minutes. The third refining slag is composed of 60 parts of quartz sand, 28 parts of lime, and 30 parts of fluorite. The addition amount is 12% of the total mass of the raw materials for ferrosilicon alloy smelting, and the overall refining time is 15 minutes. The use of the refined slag composition can reduce the aluminum content in ferrosilicon alloy to below 0.1%.
[0005] However, this refining slag composition, addition amount and overall refining time are only applicable when the aluminum content of the raw materials is very low, and are not suitable for the production of ultra-low aluminum ferrosilicon alloys using ordinary raw materials. When ordinary raw materials are used to produce ultra-low aluminum products, the aluminum content of the raw materials is high, and it is difficult to remove impurities. In order to remove the aluminum content to below 0.1%, a large amount of refining slag needs to be added, and the refining time is as long as more than 45 minutes, resulting in serious sticking losses, low ultra-low aluminum product output, and low pass rate.
[0006] In addition, appropriate calcium content can improve the organizational structure of steel, thereby improving the mechanical properties of steel; it can also improve the fluidity of molten steel, improve the surface and internal quality of ingots; and improve the corrosion resistance, wear resistance, high temperature and low temperature resistance of steel; but excessive or improper addition may cause the aggregation of high-melting-point non-metallic inclusions and lead to a decrease in steel performance, such as affecting the plasticity, toughness and fatigue strength of steel, and in severe cases, causing cracks, brittle fractures and other defects. Considering that calcium and aluminum are highly correlated during the refining and removal process, when aluminum meets the requirements, the calcium content is not the optimal value. In the steel production process, it is necessary to strictly control the calcium content to ensure that the quality and performance of the steel meet the requirements. It cannot be ignored.
[0007] Therefore, it is urgent to develop a refining method that has low raw material requirements and can produce low-calcium and ultra-low aluminum-silicon ferrosilicon alloy products. Summary of the invention
[0008] The present invention aims at the technical problems existing in the prior art and provides a method for refining ferrosilicon alloy. The method adopts the ladle bottom blowing method to add refining slag to the mixed raw materials during the iron-tapping process for refining, and at the same time, the refining of ferrosilicon alloy products with low calcium and ultra-low aluminum content is achieved by regulating the flow rate of air and oxygen in the mixed blowing gas. The method can adapt to the refining of ferrosilicon alloys with high input impurity content, and the product qualification rate is high.
[0009] The technical solution of the present invention is as follows:
[0010] The present invention provides a method for refining ferrosilicon alloy, comprising the following steps:
[0011] (1) Mix silica, carbon and iron products evenly and put them into an electric arc furnace;
[0012] (2) using the ladle bottom blowing method to add refined slag to the mixed raw materials during the iron-tapping process for refining; specifically, using air blowing before iron-tapping, adding refined slag and using mixed blowing gas blowing during the iron-tapping process, and continuing to maintain mixed blowing gas blowing after the iron-tapping is completed;
[0013] (3) After completion, remove the slag from the package and cast it into shape;
[0014] The air flow rate in the mixed blowing gas is 5-20m 3 / h, pressure is 0.6-1MPa; oxygen flow rate is 5-10m 3 / h, pressure is 0.6-1.2MPa.
[0015] In some embodiments of the present invention, the refined slag includes quartz sand; that is, the refined slag is at least quartz sand, and can also be quartz sand combined with other types of refined slag, but for process cost considerations, only quartz sand can be used.
[0016] Furthermore, the SiO2 content in the quartz sand is higher than 95%.
[0017] Furthermore, the particle size of the quartz sand used is in the range of 1-5 mm.
[0018] Furthermore, the amount of the refined slag added is 6-10% of the mass of the molten iron.
[0019] Furthermore, the air flow rate in the mixed blowing gas is 6-15m 3 / h, pressure is 0.7-0.9MPa; oxygen flow rate is 5-8m 3 / h, the pressure is 0.6-0.8MPa.
[0020] Preferably, the air flow rate in the mixed blowing gas is 9m 3 / h, pressure is 0.8MPa; oxygen flow rate is 6m 3 / h, the pressure is 0.7MPa.
[0021] Furthermore, after the iron is tapped, the mixed blowing gas blowing is continued for 10-15 minutes.
[0022] In some other embodiments of the present invention, the refined slag includes quartz sand and lime, or quartz sand, lime and calcite. That is to say, the refined slag is at least a combination of quartz sand and lime, and can also be combined with other types of refined slag such as calcite, but for the consideration of process cost, quartz sand, lime and calcite are preferred.
[0023] On the one hand, lime and calcite increase the basicity of slag, reduce the viscosity of slag, and reduce the loss of sticking. On the other hand, the heat released during the reaction of lime and calcite slows down the cooling rate of molten iron, further reducing the loss of sticking. The CO2 released by calcite during the reaction also has a stirring effect, which can improve the efficiency of dealuminization.
[0024] Furthermore, the particle size of the quartz sand used is in the range of 1-15 mm.
[0025] Furthermore, the SiO2 content in the quartz sand is higher than 96%; the CaO content in the lime is higher than 85%; and the CaCO3 content in the calcite is higher than 90%.
[0026] Preferably, the refined slag comprises, by weight, 58-62 parts of quartz sand, 19-23 parts of lime and 17-21 parts of calcite.
[0027] Further preferably, the refined slag is 60 parts of quartz sand, 22 parts of lime and 18 parts of calcite by weight;
[0028] Furthermore, the amount of the refined slag added is 10-14% of the mass of the molten iron.
[0029] Furthermore, the air flow rate in the mixed blowing gas is 8-20m 3 / h, pressure is 0.6-1MPa; oxygen flow rate is 6-10m 3 / h, pressure is 0.6-1.2MPa;
[0030] Preferably, the air flow rate in the mixed blowing gas is 14m 3 / h, pressure is 0.7MPa; oxygen flow rate is 8m 3 / h, the pressure is 1.0MPa.
[0031] Furthermore, after the iron is tapped, the mixed blowing gas blowing is continued for 20-30 minutes.
[0032] In the present invention, the amount of raw materials silica, carbon materials and iron products is based on the target product type, and the raw material amount can be calculated by the content of main elements in the raw materials silica, lignite and iron products, including but not limited to 1.8:1.1:0.4.
[0033] Furthermore, the carbon material is lignite or low-calcium lignite; and the iron product is pelletized ore.
[0034] Furthermore, the air flow rate before iron tapping is 10-20m 3 / h.
[0035] In the present invention, the role of air is to keep the molten iron churning, so that impurities and quartz sand can be better contacted and reacted to remove impurities. The role of oxygen is to keep warm on the one hand, and to supply oxygen on the other hand, so that impurities are removed in the form of oxides, which can accelerate the removal rate of aluminum and slow down the cooling rate of the molten iron, reducing the sticking loss. The refining method of quartz sand + mixed gas blowing can ensure that the obtained product meets the requirements of low-calcium ferrosilicon alloy. The refining method of quartz sand, lime and calcite refining slag + mixed gas blowing can ensure that the obtained product meets the requirements of ultra-low aluminum ferrosilicon alloy.
[0036] In addition, increasing the amount of refined slag or extending the blowing time of the mixed gas can further reduce the aluminum and calcium contents in the ferrosilicon alloy. However, within the amount and blowing time range specified in the present invention, the effects of the refined slag and the blowing gas can be maximized. Although further increasing the amount of refined slag or extending the blowing time can further reduce the aluminum content, it will result in an increase in raw material and time costs, and the refining efficiency cannot be guaranteed.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The present invention adopts the ladle bottom blowing method to add refining slag to the mixed raw materials during the iron-tapping process for refining. By using mixed blowing gas during the iron-tapping process and controlling the flow rates of compressed air and oxygen, the method can adapt to the refining of ferrosilicon alloys with high input impurity content and can effectively remove impurities such as aluminum and calcium therein.
[0039] At the same time, the present invention refines ferrosilicon alloy with a calcium content within the optimal range for steel by optimizing the combination of carbon material and refined slag, which can give full play to the advantages of calcium in steel; in addition, by controlling the particle size of the refined slag-quartz sand, the refining effect is further improved and the calcium removal rate is accelerated; at the same time, for ultra-low aluminum ferrosilicon alloy, the aluminum removal rate can reach more than 95%.
[0040] The method effectively solves the problems of high raw material requirements for low-calcium and ultra-low aluminum-silicon ferroalloys, large amount of ultra-low aluminum-silicon ferroalloy refining slag addition, long refining time, large sticking loss, and low product yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a low-calcium ferrosilicon alloy refining flow chart of Example 1 of the present invention;
[0042] Figure 2 This is a flow chart of refining ultra-low aluminum-silicon ferrosilicon alloy according to Example 3 of the present invention. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It is worth noting that the raw materials used in the present invention are all common commercial products, and their sources are not specifically limited.
[0044] The SiO2 content in the quartz sand used in the specific implementation of the present invention is 98.5%; the CaO content in the lime is 90%; and the CaCO3 content in the calcite is 95%.
[0045] The raw materials silica, low-calcium semi-coke and pellets are mixed evenly in a mass ratio of 1.8:1.1:0.4 and used. The raw material compositions used in the comparative examples are completely consistent to ensure that the content of each element in the initial raw materials is consistent.
[0046] Example 1
[0047] A refining method for low calcium ferrosilicon alloy (refining process such as Figure 1 The specific steps are as follows:
[0048] Step 1: Mix silica, low-calcium semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0049] Step 2: Adjust the air flow to 15m before tapping 3 / h, pressure is 0.8MPa;
[0050] Step 3: After iron is tapped, adjust the air flow to 9m 3 / h, the pressure is 0.8MPa, and the oxygen flow rate is adjusted to 6m 3 / h, pressure is 0.7MPa;
[0051] Step 4: During the tapping process, quartz sand (1-5 mm in particle size) accounting for 8% of the mass of the molten iron is added for refining;
[0052] Step 5: After the iron is tapped, keep blowing the mixed gas for 15 minutes;
[0053] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0054] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0055] Example 2
[0056] A refining method for low-calcium ferrosilicon alloy, the specific steps are as follows:
[0057] Step 1: Mix silica, low-calcium semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0058] Step 2: Adjust the air flow to 15m before tapping 3 / h, pressure is 0.8MPa;
[0059] Step 3: After iron is tapped, adjust the air flow to 9m 3 / h, the pressure is 0.8MPa, and the oxygen flow rate is adjusted to 6m 3 / h, pressure is 0.7MPa;
[0060] Step 4: During the tapping process, quartz sand (1-5 mm in particle size) accounting for 10% of the mass of the molten iron is added for refining;
[0061] Step 5: After the iron is tapped, keep blowing the mixed gas for 10 minutes;
[0062] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0063] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0064] Comparative Example 1
[0065] A refining method for low-calcium ferrosilicon alloy, the specific steps are as follows:
[0066] Step 1: Mix silica, low-calcium semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0067] Step 2: Adjust the air flow rate to 15m before tapping 3 / h, pressure is 0.8MPa;
[0068] Step 3: After iron is tapped, adjust the air flow to 12m 3 / h, the pressure is 0.8MPa, and the oxygen flow rate is adjusted to 3m 3 / h, pressure is 0.7MPa;
[0069] Step 4: During the tapping process, quartz sand (1-5 mm in particle size) accounting for 8% of the mass of the molten iron is added for refining;
[0070] Step 5: After the iron is tapped, keep blowing the mixed gas for 15 minutes;
[0071] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0072] Step 7: After slag removal, pour the molten iron into the ingot mold and cool it into shape. After casting, turn on the air and adjust the flow to the maximum.
[0073] Comparative Example 2
[0074] A refining method for low-calcium ferrosilicon alloy, the specific steps are as follows:
[0075] Step 1: Mix silica, low-calcium semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0076] Step 2: Adjust the air flow rate to 15m before tapping 3 / h, pressure is 0.8MPa;
[0077] Step 3: After iron is tapped, adjust the air flow to 9m 3 / h, the pressure is 0.8MPa, and the oxygen flow rate is adjusted to 6m 3 / h, pressure is 0.7MPa;
[0078] Step 4: During the tapping process, quartz sand (6-15 mm in particle size) accounting for 8% of the mass of the molten iron is added for refining;
[0079] Step 5: After the iron is tapped, keep blowing the mixed gas for 15 minutes;
[0080] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0081] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0082] Comparative Example 3
[0083] A refining method for low-calcium ferrosilicon alloy, the specific steps are as follows:
[0084] Step 1: Mix silica, low-calcium semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0085] Step 2: Adjust the air flow to 15m before tapping 3 / h, pressure is 0.8MPa;
[0086] Step 3: After iron is tapped, adjust the air flow to 9m 3 / h, the pressure is 0.8MPa, and the oxygen flow rate is adjusted to 6m 3 / h, pressure is 0.7MPa;
[0087] Step 4: During the tapping process, quartz sand (1-15 mm in particle size) accounting for 8% of the mass of the molten iron is added for refining;
[0088] Step 5: After the iron is tapped, keep blowing the mixed gas for 15 minutes;
[0089] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0090] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0091] Example 3
[0092] A refining method for ultra-low aluminum-silicon ferroalloy (refining process such as Figure 2The specific steps are as follows:
[0093] Step 1: Mix silica, semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0094] Step 2: Adjust the air flow rate to 14m before tapping 3 / h, pressure is 0.7MPa;
[0095] Step 3: After iron is tapped, adjust the oxygen flow rate to 8m 3 / h, pressure is 1.0MPa;
[0096] Step 4: 60 parts by weight of quartz sand (particle size 1-15 mm), 22 parts of lime and 18 parts of calcite are mixed to prepare refined slag, and 12% of the mass of molten iron is added to the refined slag for refining after 5 minutes of iron tapping;
[0097] Step 5: After the iron is tapped, the mixed gas is kept blowing for 25 minutes;
[0098] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0099] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0100] Example 4
[0101] A refining method for ultra-low aluminum-silicon ferrosilicon alloy, the specific steps are as follows:
[0102] Step 1: Mix silica, semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0103] Step 2: Adjust the air flow rate to 12m before tapping 3 / h, pressure is 0.7MPa;
[0104] Step 3: After iron is tapped, adjust the oxygen flow rate to 10m 3 / h, pressure is 1.0MPa;
[0105] Step 4: 60 parts by weight of quartz sand (particle size 1-15 mm), 22 parts of lime and 18 parts of calcite are mixed to prepare refined slag, and 14% of the mass of molten iron is added to the refined slag for refining after 5 minutes of iron tapping;
[0106] Step 5: After the iron is tapped, keep blowing the mixed gas for 20 minutes;
[0107] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0108] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0109] Example 5
[0110] A refining method for ultra-low aluminum-silicon ferrosilicon alloy, the specific steps are as follows:
[0111] Step 1: Mix silica, semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0112] Step 2: Adjust the air flow to 16m before tapping 3 / h, pressure is 0.7MPa;
[0113] Step 3: After iron is tapped, adjust the oxygen flow rate to 6m 3 / h, pressure is 1.0MPa;
[0114] Step 4: 60 parts by weight of quartz sand (particle size 1-15 mm), 22 parts of lime and 18 parts of calcite are mixed to prepare refined slag, and 10% of the mass of molten iron is added to the refined slag for refining after 5 minutes of iron tapping;
[0115] Step 5: After the iron is tapped, the mixed gas is kept blowing for 30 minutes;
[0116] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0117] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0118] Comparative Example 4
[0119] A refining method for ultra-low aluminum-silicon ferrosilicon alloy, the specific steps are as follows:
[0120] Step 1: Mix silica, semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0121] Step 2: Adjust the air flow rate to 18m before tapping 3 / h, pressure is 0.7MPa;
[0122] Step 3: After iron is tapped, adjust the oxygen flow rate to 4m 3 / h, pressure is 1.0MPa;
[0123] Step 4: 60 parts by weight of quartz sand (particle size 1-15 mm), 22 parts of lime and 18 parts of calcite are mixed to prepare refined slag, and 12% of the mass of molten iron is added to the refined slag for refining after 5 minutes of iron tapping;
[0124] Step 5: After the iron is tapped, the mixed gas is kept blowing for 25 minutes;
[0125] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0126] Example 6
[0127] A refining method for ultra-low aluminum-silicon ferrosilicon alloy, the specific steps are as follows:
[0128] Step 1: Mix silica, semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0129] Step 2: Adjust the air flow rate to 14m before tapping 3 / h, pressure is 0.7MPa;
[0130] Step 3: After iron is tapped, adjust the oxygen flow rate to 8m 3 / h, pressure is 1.0MPa;
[0131] Step 4: 58 parts of quartz sand (particle size 1-15 mm), 23 parts of lime and 19 parts of calcite are mixed to prepare refined slag, and 12% of the mass of molten iron is added to the refined slag for refining after 5 minutes of iron tapping;
[0132] Step 5: After the iron is tapped, the mixed gas is kept blowing for 25 minutes;
[0133] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0134] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0135] Example 7
[0136] A refining method for ultra-low aluminum-silicon ferrosilicon alloy, the specific steps are as follows:
[0137] Step 1: Mix silica, semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0138] Step 2: Adjust the air flow rate to 14m before tapping 3 / h, pressure is 0.7MPa;
[0139] Step 3: After iron is tapped, adjust the oxygen flow rate to 8m 3 / h, pressure is 1.0MPa;
[0140] Step 4: 59 parts of quartz sand (particle size 1-15 mm), 21 parts of lime and 20 parts of calcite are mixed to prepare refined slag, and 12% of the mass of molten iron is added to the refined slag for refining after 5 minutes of iron tapping;
[0141] Step 5: After the iron is tapped, the mixed gas is kept blowing for 25 minutes;
[0142] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0143] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0144] Example 8
[0145] A refining method for ultra-low aluminum-silicon ferrosilicon alloy, the specific steps are as follows:
[0146] Step 1: Mix silica, semi-coke and pellets in a mass ratio of 1.8:1.1:0.4 and put them into an electric arc furnace for smelting;
[0147] Step 2: Adjust the air flow rate to 14m before tapping 3 / h, pressure is 0.7MPa;
[0148] Step 3: After iron is tapped, adjust the oxygen flow rate to 8m 3 / h, pressure is 1.0MPa;
[0149] Step 4: 62 parts of quartz sand (particle size 1-15 mm) and 20 parts of lime are mixed to prepare refined slag by weight, and 12% of the mass of molten iron is added to the refined slag for refining 5 minutes after the iron is tapped;
[0150] Step 5: After the iron is tapped, the mixed gas is kept blowing for 25 minutes;
[0151] Step 6: After the blowing is completed, the mixed gas is turned off and the ladle is moved to the slag removal platform to remove slag;
[0152] Step 7: After slagging, pour the molten iron into the ingot mold, then turn on the air, adjust the flow to the maximum, and cool it into shape.
[0153] In addition, the slag production using only quartz sand and lime can also achieve a refining effect close to that of quartz sand, lime and calcite, but the cost is higher.
[0154] The silicon content, aluminum content, calcium content, aluminum removal rate and calcium removal rate of the ferrosilicon alloys obtained by comparative refining in the above embodiments are shown in Table 1.
[0155] Table 1
[0156]
[0157] As can be seen from the above table, when the refining method of the present invention uses low-calcium semi-coke as raw material, the control of air and oxygen flow after iron tapping can obtain ferrosilicon alloy with a lower appropriate calcium content, which can give full play to the advantages of calcium in steel; in addition, for conventional carbon materials, more than 95% of aluminum can be removed by controlling the air and oxygen flow after iron tapping, and aluminum can be removed to an ultra-low level when the aluminum level entering the furnace is high. It can meet the needs of large furnaces to produce ultra-low aluminum products, and the effect is better in small furnaces.
[0158] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for refining ferrosilicon alloy, characterized in that: The following steps are involved: (1) Mix silica, carbon and iron products evenly and put them into an electric arc furnace; (2) using the ladle bottom blowing method to add refined slag to the mixed raw materials during the iron-tapping process for refining; specifically, using air blowing before iron-tapping, adding refined slag and using mixed blowing gas blowing during the iron-tapping process, and continuing to maintain mixed blowing gas blowing after the iron-tapping is completed; (3) After completion, remove the slag from the ladle and cast into shape; The air flow rate in the mixed blowing gas is 5-20m 3 / h, pressure is 0.6-1MPa; oxygen flow rate is 5-10m 3 / h, pressure is 0.6-1.2MPa.
2. The refining method according to claim 1, characterized in that: The carbon material is low-calcium blue carbon, the iron product is pelletized ore; the refined slag includes quartz sand; and the amount of the refined slag added is 6-10% of the mass of the molten iron.
3. The refining method according to claim 2, characterized in that: The particle size of the quartz sand is 1-5 mm; the SiO2 content in the quartz sand is higher than 95%.
4. The refining method according to claim 2, characterized in that: The air flow rate in the mixed blowing gas is 6-15m 3 / h, pressure is 0.7-0.9MPa; oxygen flow rate is 5-8m 3 / h, the pressure is 0.6-0.8MPa; preferably, the air flow rate in the mixed blowing gas is 9m 3 / h, pressure is 0.8MPa; oxygen flow rate is 6m 3 / h, the pressure is 0.7MPa.
5. The refining method according to claim 2, characterized in that: After the iron is tapped, continue blowing with the mixed blowing gas for 10-15 minutes.
6. The refining method according to claim 1, characterized in that: The carbon material is lignite, and the iron product is pelletized ore; the refined slag includes quartz sand and lime, or quartz sand, lime and calcite; preferably, the refined slag is 58-62 parts by weight of quartz sand, 19-23 parts by weight of lime and 17-21 parts by weight of calcite; further preferably, it is 60 parts by weight of quartz sand, 22 parts by weight of lime and 18 parts by weight of calcite; the amount of refined slag added is 10-14% of the mass of molten iron.
7. The refining method according to claim 6, characterized in that: The particle size of the quartz sand is 1-15 mm; the SiO2 content in the quartz sand is higher than 96%; the CaO content in the lime is higher than 85%; and the CaCO3 content in the calcite is higher than 90%.
8. The refining method according to claim 6, characterized in that: The air flow rate in the mixed blowing gas is 8-20m 3 / h, pressure is 0.6-1MPa; oxygen flow rate is 6-10m 3 / h, the pressure is 0.6-1.2MPa; preferably, the air flow rate in the mixed blowing gas is 14m 3 / h, pressure is 0.7MPa; oxygen flow rate is 8m 3 / h, the pressure is 1.0MPa.
9. The refining method according to claim 6, characterized in that: After the iron is tapped, continue blowing with the mixed blowing gas for 20-30 minutes.
10. The refining method according to claim 1, characterized in that: The air flow rate before iron tapping is 10-20m 3 / h.
Citation Information
Patent Citations
Refining slag composition with aluminum content lower than 0.1% and for silicon iron external refining
CN112375874A